뿌리혹선충 Meloidogyne incognita에 대한 저항성 고추를 선발하기 위한 효율적인 검정법 확립 - 최용호(Yong Ho Choi); 최경자(Gyung Ja Choi); 장경수(Kyoung Soo Jang); 황성민(Sung Min Hwang) (Weon'ye gwahag gi'sulji, 2016)
Root-knot nematodes (Meloidogyne spp.) are major plant pathogens that cause reductions in yield and quality of several solanaceous crops, including pepper (Capsicum spp.). These losses can be averted through planting of resistant cultivars. Plants are defined as resistant when they suppress nematode reproduction. In this study, the resistance degrees of 102 commercial cultivars of chili pepper (Capsicum annuum) to a root-knot nematode, Meloidogyne incognita, were evaluated by comparing the number of egg masses on their roots to those of 'PR huimangchan', a highly susceptible cultivar that exhibited the most egg masses of the chili pepper cultivars evaluated. Among these cultivars, forty-four (43.1%) showed resistance to M. incognita and eighteen (17.6%) were moderately resistant. The other cultivars (39.3%) were determined to be susceptible. For further study, six chili pepper cultivars (i.e., Gangryeokjosenggeon, Shinsegae, Muhanjilju, PR Bulrocho, PR Huimangchan, and Jjang) with different levels of resistance to the nematode were selected. Changes in resistance of the six cultivars under several conditions, such as inoculum concentration, plant growth stage, and cultivation period after transplanting were investigated. We found that an efficient screening method for resistance of chili pepper to M. incognita is to transplant the chili pepper seedlings 7 days before inoculation, to inoculate 28-day-old plants with M. incognita by loading 5,000 eggs per plant into the pot of soil, to cultivate the plants in a greenhouse ($25{±}5^{°}C$) for 45-60 days, to measure the number of egg masses on roots of the seedlings, and then to determine the resistance response of the plants by comparing the number of egg masses on the roots with a reference-susceptible cultivar 'PR huimangchan'. 뿌리혹선충(Meloidogyne spp.)은 고추(Capsicum spp.)를 포함한 여러 가지과 작물에서 경제적인 손실을 일으키는 주요 식물 병원균 중 하나이다. 이러한 뿌리혹선충에 의한 작물의 피해는 친환경적인 방제법인 저항성 품종의 재배로 줄일 수 있다. 선충병에서는 식물에서 선충의 후대생산이 억제되었을 때 그 식물을 저항성으로 간주한다. 시판 중인 고추(Capsicum annuum) 품종 102개의 뿌리혹선충(Meloidogyne incognita)에 대한 저항성 정도를 감수성 대조 품종인 'PR 희망찬'에 형성된 난낭의 수와 비교하여 평가하였다. 실험한 고추 품종 중 44개 품종(43.1%)은 저항성을 그리고 18개 품종(17.6%)은 중도저항성을 보였다. 그리고 나머지 40개 품종(39.3%)은 감수성을 나타냈다. 그리고 뿌리혹선충(M. incognita)에 의해 발생하는 고추 뿌리혹선충병에 대한 효율적인 저항성 검정법을 확립하기 위하여 실험한 품종 중 저항성 정도가 다른 6개 품종을 선발하였다. 그리고 이들 6개 고추 품종의 접종원 농도, 고추 생육 시기 및 이식 후 배양 기간 등의 발병 조건에 따른 뿌리혹선충에 대한 저항성 차이를 조사하였다. 발병 조건에 따른 품종들의 저항성 차이 결과들을 바탕으로 M. incognita에 대한 고추의 저항성 정도를 검정하기 위한 효율적인 방법으로 온실($25{±}5^{°}C$)에서 21일 동안 재배한 고추 유묘를 원예용 상토와 모래의 혼합토(1:1, v/v)에 이식하고 7일 동안 재배한 고추 유묘에 뿌리혹선충 M. incognita 알 5,000개를 접종하고 온실에서 45-60일 동안 재배하고, 뿌리에 형성된 난낭의 수를 조사하여 감수성 대조 품종인 'PR 희망찬'에 형성된 난낭 수와 비교하여 저항성을 판정하는 방법을 제안한다.